Competitive drivers and international plant configuration strategies: a product‐level test - Belderbos, Ren; Sleuwaegen, Leo (Strategic Management Journal, 2005)
Abstract We analyze the determinants of the decision to invest abroad and the choice of spatial configurations of overseas plants for 120 Japanese firms active in 36 well‐defined electronic product markets. We find that key competitive drivers at the firm and industry levels have a critical impact on the choice between alternative international plant configurations. Regional configurations focused on Asia are chosen by firms with weaker competitiveness for products with established manufacturing technologies. Plant configurations focused on the United States and the European Union are chosen by technology‐intensive firms facing competitive threats in foreign markets. Global configurations are chosen by firms with a strong competitive position in the Japanese and world market for their core product businesses and are more common in the case of strong oligopolistic rivalry between Japanese firms. Copyright © 2005 John Wiley & Sons, Ltd.